Penerapan Pendekatan Kooperatif Jigsaw Memorizer untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Pada Mata Pelajaran PKn Kelas IV SD Negeri 38 Rejang Lebong - Rasuna, Rasuna (AR-RIAYAH : Jurnal Pendidikan Dasar, 2017)
This study aims to increase student activity with the implementation of Cooperative Approaches Jigsaw Memorizer on Civics Lesson in the class IV Elementary School 38 Rejang Lebong. And to improve student achievement in learning civics with the implementation school 38 Rejang Lebong. The problems of this study are: Does the implementation of Cooperative Approaches Jigsaw Memorizer can enhance studentsâ active learning in civics class IV Elementary school 38 Rejang Lebong? And is Jigsaw Cooperative Learning Approach Memorizer can improve student learning outcomes civics class IV elementary school 38 Rejang Lebong?. Kind of research is a class action research (classroom action research) couduceted in two cycles using two variabels, namely the independent variabel is a Cooperative Approach Jigsaw Memorizer while thw dependent variabel is the studentâs activity and student achievement. The instruments in this study is the observation sheet and test sheet. The subjects were students/ student and 14 female students .. Observation data were analyzed descriptively by looking at average scores, the criteria scores, the range of values each criteria, the difference in scores, te highest score, the lowest score. The test data were analyzed qualitatively using the formula avarage value of students and the percentage of students in the classical absorption. Thus obtained result of a study of the activity of students and teachers that the student activity than the average score of 22.75 with the criteria both the firts cycle to 29.25 with really good criteria in the second cycle, while the activity of the teacher than the average score of 35.25 neither the criteria in the firts cycle increased to 41.25 with the criteria neither the criteria in the first cycle students average score of 6.82 with the percentage of students absorption of 64%, while in the second cycle students average score 8.56 with the percantage of students 92% absorption. Based on these studies, the implementation of cooverative aproaches to learning civicis igsaw memorizer can enchance the activity and student achievement in fourth grade rejang state 38 lebong.